The Influence Of Islamic Boarding School Culture On The Character Building Of Santri At Queen Al-Falah Islamic Boarding School Ploso Kediri - Virgin Sabrina El-Islamy; Firda Al Husnia; Nurul Yaqien; Lukman Sholeh (Relevancia: Jurnal Pendidikan dan Pembelajaran, 2025)
The purpose of this study was to determine the influence of pesantren culture on the formation of the character of students at the Sirojul Ulum Pare Kediri Islamic Boarding School. In this study using a quantitative approach, in which researchers collected data using questionnaires, interviews and documentation. The method used in this research is inferential analysis method with multiple linear regression analysis. Sampling of 40 students. The results of this study indicate that the influence of Islamic boarding school culture on the formation of the character of the students at the Queen Al-Falah Ploso Islamic Boarding School, Kediri, has a strong and significant influence of 27.3%, meaning that the culture of the Islamic boarding school is significantly related to the formation of the character of the students. Meanwhile, 72.7% is determined by other factors.